Cestode Parasites of Birds of Suborder Charadrii from Syvash Lake, Ukraine - Greben, О.B. (Вестник зоологии, 2013)
Twelve birds species of the suborder Charadrii of the families Charadriidae, Recurvirostridae, Scolopacidae, Glareolidae were examined at Syvash Lake (Ukraine) in spring 2011. Cestodes were found in 82.1 % of examined birds. Seventeen cestode species of 6 families were found. Aploparaksis octacantha from Calidris alpinа and Echinocotyloides dubininae from C. ferruginea are new geographical records for the first time in Ukraine. Glareola pratincola is a new host record for Nadejdolepis paranitidulans. Cestodes of the genus Microsomacanthus were found in waders apparently due to the infection (2.8 %) in their intermediate hosts, gammarid crustaceans. Весной 2011 г. на озере Сиваш (Украина) было исследовано 12 видов куликов подотряда Charadrii, семейств Charadriidae, Recurvirostridae, Scolopacidae, Glareolidae. У 82.1 % исследованных птиц найдены цестоды. Обнаружено 17 видов цестод 6 семейств. Aploparaksis octacantha от C. alpinа и Echinocotyloides dubininae от C. ferruginea впервые зарегистрированы в Украине. Для Nadejdolepis paranitidulans указан новый хозяин — Glareola pratincola. У куликов также найдены представители рода Microsomacanthus, что связано с заражённостью (2,8 %) промежуточных хозяев, гаммарусов.